2019
DOI: 10.12998/wjcc.v7.i22.3844
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic segmentectomy assisted by three-dimensional computed tomography bronchography and angiography for lung cancer in a patient living with situs inversus totalis: A case report

Abstract: BACKGROUNDSitus inversus totalis (SIT) is a rare congenital condition that is characterized by a complete mirror image of the typical arrangement of the thoracic and abdominal viscera. Performing thoracoscopic segmentectomy for a patient with lung cancer and SIT is an extremely skilled and challenging surgical procedure.CASE SUMMARYA 41-year old woman with a medical history of dextrocardia since childhood was admitted to our hospital with a mixed ground-glass opacity (mGGO) in her left lung field, discovered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Only eight studies reported a follow-up (6 months-2 years). The majority of cases were described in the eastern part of the world [15,18,19,21,22,[24][25][26][28][29][30][31]33,34]. Surprisingly, the presence of as many as three such cases was observed in Szczecin, in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only eight studies reported a follow-up (6 months-2 years). The majority of cases were described in the eastern part of the world [15,18,19,21,22,[24][25][26][28][29][30][31]33,34]. Surprisingly, the presence of as many as three such cases was observed in Szczecin, in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The complex anatomy in SIT is a difficulty in the preoperative planning of thoracic procedures. Therefore, 3D-CT images were described in several included articles [28,29,33,34]. It is important to remember potential metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this surgical procedure in SIT patients with lung carcinoma, although previous reports showed cases of segmentectomy, lobectomy or pneumonectomy with the help of VATS, we did not find any case with the use of RATS in our literature review. Although Baruah [27] first reported the case of lung cancer with SIT in 1952 and Kodama performed the first lung cancer surgery in SIT patient in 1990 [28], surgery qualification for lung cancer/SIT patients is still difficult as there is a little experience of less than 30 lung cancer/SIT patients operation so far, among which only eleven cases were performed with video-assisted thoracic surgery [1,13,[29][30][31][32][33][34][35][36][37]. The majority of the study group was male (8/11), and adenocarcinoma was the most frequent pathological type (7/11).…”
Section: Discussionmentioning
confidence: 99%
“…This information can be difficult to capture from Computed Tomography (CT) alone. Standardof-care multi-detector CT images, enhanced with contrast agent for better delineation of the pulmonary vasculature, was first combined with volume rendering software to provide a threedimensional (3D) image of the patient's specific anatomy (9)(10)(11). More recently, modern medical image segmentation software has been applied to the contrast-enhanced CT scans to produce separable surface representations of the anatomical components (e.g., arterial, venous and bronchial systems).…”
Section: Introductionmentioning
confidence: 99%